Older and younger adults differ in time course of skill acquisition but not in overall improvement in a bimanual visuomotor tracking task - Zvornik, Ana; Andersen, Keenie Ayla; Petersen, Andreas Deigaard; Novén, Mikael; Siebner, Hartwig Roman; Lundbye-Jensen, Jesper; Karabanov, Anke Ninija (Frontiers in Aging Neuroscience, 2024)
Manual motor performance declines with age but the extent to which age influences the acquisition of new skills remains a topic of debate. Here, we examined if older healthy adults show less training dependent performance improvements during a single session of a bimanual pinch task than younger adults. We also explored whether physical and cognitive factors, such as grip strength or motor-cognitive ability are associated with performance improvements. Healthy younger (n =16) and older (n = 20) adults performed three training blocks separated by short breaks. Participants were tasked with producing visually instructed changes in pinch force using their right and left thumb and index finger. Task complexity was varied by shifting between bimanual mirror-symmetric and inverseasymmetric changes in pinch force. Older adults generally displayed higher visuomotor force tracking error during the more complex inverse-asymmetric task compared to the younger adults. Both groups showed a comparable net decrease in visuomotor force tracking error over the entire session but their improvement trajectories differed. Young adults showed enhanced visuomotor tracking error only in the first block, while older adults exhibit a more gradual improvement over the three training blocks. Furthermore, grip strength and performance on a motor-cognitive test battery scaled positively with individual performance improvements during the first block in both age groups. Together, the results show subtle age-dependent differences in the rate of bimanual visuomotor skill acquisition, while overall short-term learning ability is maintained.